Aberrant expressions of endometrial Id3 and CTLA‐4 are associated with unexplained repeated implantation failure and recurrent miscarriage. (21st February 2017) - Ding, Jin‐Li; Diao, Liang‐Hui; Yin, Tai‐Lang; Huang, Chun‐Yu; Yin, Biao; Chen, Cong; Zhang, Yi; Li, Jie; Cheng, Yan‐Xiang; Zeng, Yong; Yang, Jing
Abstract : Inhibitor of DNA‐binding protein 3 (Id3) is required for tumor angiogenesis and regulatory T‐cell generation. However, the involvement of Id3 in unexplained repeated implantation failure (RIF) and recurrent miscarriage (RM) remains poorly understood. Immunohistochemistry was used to identify Id3, CD34, CTLA‐4, and FOXP3 in the endometrium taken from the women with RIF (n=16), RM (n=16) and matched controls (n=8). The images were acquired and analyzed by the Vectra ® automated quantitative pathology imaging system. Percentage of Id3 + cells was significantly higher in the endometrium of women with RIF and RM compared with controls. The numbers of Id3 + and CD34 + vessels in the endometrium were positively correlated in control but not in RIF or RM. Percentages of CTLA‐4 + cells, but not FOXP3 + cells, were significantly increased in the endometrium of RIF and RM women than those in controls. We found aberrant expressions of endometrial Id3 and CTLA‐4 in peri‐implantation endometrium of women with RIF and RM, suggesting the negative roles of these angiogenesis and immune tolerance markers involving in regulating endometrium receptivity.